Microsporidial Keratoconjunctivitis Caused by Vittaforma corneae, Sea of Galilee, Israel, 2022–2024 - Asaf Friehmann; Irit Lubitz; Fidaa El Zhalka; Sharon Amit (Emerging Infectious Diseases)
We describe a multiannual outbreak of keratoconjunctivitis caused by the microsporidium Vittaforma corneae in the Sea of Galilee, Israel. Patients had multifocal punctate corneal infiltrates and reduced visual acuity, confirmed by locally-developed pathogen-specific real-time PCR. Topical chlorhexidine, rather than traditional antimicrobial drugs, proved an effective and safe primary treatment.